Human, Technologies and Quality of Education, 2022 2022
DOI: 10.22364/htqe.2022.11
|View full text |Cite
|
Sign up to set email alerts
|

Digital Transformation in Higher Education: Drivers, Success Factors, Benefits and Challenges

Abstract: Digital transformation (DT) is rapidly penetrating all spheres of human life, and higher education is no exception. This process is inevitable and ensures competitive advantage and other benefits for Higher Education Institutions (HEI) in case of success. Due to the COVID-19 pandemic, HEIs worldwide were forced to completely transform their working methods and go digital in a very short period. Some institutions are more successful in this transformation by possessing the ability to overcome DT challenges and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Several research endeavors and authorial groups have emphasized the pivotal role played by information technology infrastructure and strategies for its application in determining the success or failure of businesses' digital transformation. Osmundsen et al [6] identified information technology infrastructure as one of the eight critical factors affecting digital transformation activities. In contrast, the readiness of human resources for digital transformation was underscored by Marzenna et al [7].…”
Section: Related Workmentioning
confidence: 99%
“…Several research endeavors and authorial groups have emphasized the pivotal role played by information technology infrastructure and strategies for its application in determining the success or failure of businesses' digital transformation. Osmundsen et al [6] identified information technology infrastructure as one of the eight critical factors affecting digital transformation activities. In contrast, the readiness of human resources for digital transformation was underscored by Marzenna et al [7].…”
Section: Related Workmentioning
confidence: 99%